Ajaran Agama Hindu Dalam Kakawin Mayaspati - Ida Bagus Wika Krishna (Pramana: Jurnal Hasil Penelitian, 2022)
Kakawin is one of the Old Javanese literary works which is essentially bound by the metrum (guru laghu) which has developed rapidly in Java. After the collapse of the Majapahit Kingdom in the 15th century, Old Javanese literature experienced a decline, eventually moving to Bali. Until now, efforts to save ancestral heritage in Bali continue to be carried out by clearly copying these literary works. Kakawin received considerable attention from the Balinese people, especially among lovers of classical literature. This is proven by the existence of free groups (pesantian groups) in almost every village in Bali. Kakawin Mayaspati has many interesting things to study because Kakawin Mayaspati contains moral messages that are conveyed through the character of each characterization. In addition, Kakawin Mayaspati also has an appeal in every episode of the story, meaning that each stage or incident has a value that needs to be imitated or not at all. Examples of good and bad deeds so that Kakawin Mayaspati contains religious values, especially Hinduism. Theories used to solve research problems are: (1) Structural Theory, (2) Value Theory. This research is in the form of a qualitative design. Data were collected using document techniques and interview techniques. After the data was collected, the data were analyzed using descriptive qualitative techniques. Based on this analysis, conclusions were obtained as a result of the research, as follows: (1) Kakawin Mayaspati's Narrative Structure which includes Incident, Plot, Setting, Characterization, Theme and Mandate of Kakawin Mayaspati. (2) The teachings contained in Kakawin Mayaspati which include the teachings of Karma Phala, these teachings are contained in the quote from Kakawin Mayaspati XXII: 45a Mayaspati III: 10a and 11a, the teachings of Tri Kaya Parisudha especially about Kayika, the teachings of Tri Kaya Parisudha especially Kayika are contained in Mayaspati VI quote: 14a stanza 4 and 14b stanza 4 and Mayaspati XXX: 63b. and the teachings of Tri Hita Karana are mainly emphasized on the Palemahan element, the teachings of Tri Hita Karana especially Palemahan are contained in Mayaspati XI quotes: 25a stanza 2 and 26a stanza 2.